MORBIDITY WITH SYPHILIS AND GONORRHEA IN CHILDREN IN RUSSIAN FEDERATION: REGIONAL DIFFERENCES IN 2000-2006 YEARS - A.I. Novikov; Zh.V. Gudinova; A.A. Nikitin ("Paediatrician" Publishers LLC, 2009)
The data on children's under the age of 14 years old morbidity with syphilis and gonorrhea analysis around the territory of the Russian Federation during the period from 2000 to 2006 are presented in this article. It is mentioned that the rate of children's morbidity with syphilis has always been 2 times higher than by gonorrhea. The decrease of rate of children's morbidity in Russia with syphilis is reduced twice, with gonorrhea - in 2.4 times. Authors detected essential interregional variability of rates, with the best results in European and South part of the country and with the worst results in Siberia and in the Far East. The social macroeconomic and national factors of children's morbidity formation with syphilis and gonorrhea in Russia, and the various quality of registration of the pathology in regions of the country are supposed. Key words: children, syphilis, gonorrhea, morbidity. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):32-36)